Price level targeting and risk management - Roberto Billi (Sveriges Riksbank, 2015)
Many argue that, in the presence of a lower bound on nominal interest rates, central banks should use a risk management approach for setting policy, which implies commit- ting to a more expansionary policy to deal with uncertainty about the economic recovery. Using a standard model for monetary policy analysis, I study the effects of an uncertain future for both price level targeting and nominal GDP level targeting. The results clarify that, during lower bound episodes, the extent to which policy can overcome uncertainty depends crucially on the choice of policy framework.
Keywords: E31; E52; E58; 330; nominal level targets; optimal discretionary policy; zero lower bound